Clinical, Metabolic and Hormonal Overlap Between Nonclassic Congenital Adrenal Hyperplasia and Polycystic Ovary Syndrome: An Exploratory Study - Arzu Yavuz; Aylin Coskun; Dilara Tekin Uzman; Esra Hatipoglu (Journal of Clinical Medicine, 2026)
Objective: Polycystic ovary syndrome (PCOS) and nonclassic congenital adrenal hyperplasia (NCAH) overlap clinically, but direct comparative data specifically addressing non-National Institutes of Health (non-NIH) Rotterdam phenotypes of polycystic ovary syndrome are limited. We compared women with polycystic ovary syndrome, of whom 66.7% were classified as having non-NIH Rotterdam phenotypes, with women with nonclassic congenital adrenal hyperplasia and healthy controls to characterize the extent of phenotypic overlap and evaluate the discriminatory performance of individual androgen measures. Methods: This single-center, prospective, exploratory cross-sectional study evaluated 58 women divided into three groups: PCOS (n = 24, Rotterdam criteria), NCAH due to 21-hydroxylase deficiency (n = 16, previously confirmed by adrenocorticotropic hormone (ACTH)-stimulated 17-hydroxyprogesterone (17-OHP)), and healthy controls (n = 18). Demographic, clinical, metabolic, and hormonal parameters were compared using analysis of variance (ANOVA), Kruskal–Wallis with Dunn’s post hoc test (Bonferroni-adjusted), and chi-square or Fisher’s exact tests. A sensitivity analysis was performed after excluding 12 participants receiving oral contraceptives (n = 8) or glucocorticoids (n = 4). Results: Within the PCOS group, 66.7% had non-NIH Rotterdam phenotypes. Hirsutism, defined as a modified Ferriman–Gallwey (mFG) score ≥ 8, was more frequent in both patient groups than in controls (p = 0.003) but did not differ between PCOS and NCAH. Total testosterone levels were 0.40 [0.20–0.60], 0.59 [0.45–0.94], and 0.20 [0.15–0.20] ng/mL in the PCOS, NCAH, and control groups, respectively, and androstenedione levels were 1.40 [1.20–2.20], 2.55 [1.64–4.07], and 0.87 [0.56–1.00] ng/mL, respectively; both were higher in the patient groups than in controls (both p < 0.001), without differing between PCOS and NCAH. Basal 17-OHP was the only parameter distinguishing NCAH from both PCOS and controls (p < 0.001). Dehydroepiandrosterone sulfate (DHEAS) levels were 356.5 [217–422], 292 [156–448], and 219 [146–240] µg/dL, respectively (p = 0.020), with a significant difference only between PCOS and controls. Anti-Müllerian hormone (AMH) levels were 3.27 [3.02–4.13], 3.13 [2.87–3.54], and 3.34 [2.93–5.37] ng/mL, respectively, with no between-group difference (p = 0.600). Other metabolic parameters, gonadotropins, estradiol, and prolactin showed no between-group differences. The principal hormonal findings remained unchanged after excluding women receiving oral contraceptives or glucocorticoids. Conclusions: In this PCOS cohort, in which 66.7% of women were classified as having non-NIH Rotterdam phenotypes, PCOS and NCAH showed substantial clinical, metabolic, and hormonal overlap, whereas basal early-follicular 17-OHP was the only parameter that consistently distinguished NCAH from both PCOS and healthy controls. These findings support the inclusion of basal 17-OHP in the evaluation of women presenting with hyperandrogenism.